The berbers of the fields in the Sahara of the Central Maghreb and its northern Outskirts from the Islamic conquest to the end of the 3AH⁄9AD - benarib, moustafa (The Algerian Historical Journal, 2026)
This resarch deals with the Berbers of the fields in the Sahara of the Central Maghreb and its outskirts from the conquest to the end of the 3AH/9AD, as a form of tribal settlement presented by Ibn Khaldun during his history and represents the areas scattered in the northern sahara edges of Central Maghreb and extending along the hills and areas located South Erg near Sudan ,home to the Bedouin tribes of the great nomads ,where Zenata and some of the tribes of Al-Botar were able to dominate its northern areas and Outskirts of its sahara.On the other hand ,Elmolathamoun spread to its southern areas behind Al-Irg .The nature of Sahra contributed to imposing certain types of economic activity like breeding camels, raiding weak tribes and caravans or guide and securing them for huge money.